MAXIMUM POWEWR POINT TRACKING SYSTEM FOR PHOTOVOLTAIC STATION: A REVIEW - I. Elzein (Системный анализ и прикладная информатика)
In recent years there has been a growing attention towards the use of renewable energy sources. Among them solar energy is one of the most promising green energy resources due to its environment sustainability and inexhaustibility. However photovoltaic systems (PhV) suffer from big cost of equipment and low efficiency. Moreover, the solar cell V-I characteristic is nonlinear and varies with irradiation and temperature. In general, there is a unique point of PhV operation, called the Maximum Power Point (MPP), in which the PV system operates with maximum efficiency and produces its maximum output power. The location of the MPP is not known in advance, but can be located, either through calculation models or by search algorithms. Therefore MPPT techniques are important to maintain the PV array’s high efficiency. Many different techniques for MPPT are discussed. This review paper hopefully will serve as a convenient tool for future work in PhV power conversion.